Multi-scale strategies in environmental education, that pursue appreciation of the natural and rural areas of the Mediterranean mountains, in southern Spain - Luque-Revuelto, Ricardo Manuel; Molero-Baltanás, Rafael (Revista de Estudios Andaluces, 2022)
The meridional mountains of Europe are located in Andalusia, in the south of the Iberian Peninsula. In this region, orographic and climatic factors are the main circumstances that condition the landscape and cultural peculiarities. Nowadays, its ecosystems show a high vulnerability to climate change, its traditional ways of life are in crisis and its cultural heritage is endangered by abandonment and depopulation. This paper analyzes some of the main documents that include proposals of environmental education at European, national and regional levels from the point of view of its adaptation the territory of the Andalusian Mediterranean mountains. Some educational actions are also evaluated in order to detect the possible existence of dysfunctionalities or deficiencies among the different educational policies and projects. Finally, a series of actions are proposed to optimize environmental education programs.